(untitled) (Práxis Educativa, 2022)
The article discusses the results of a research involving educators from a public school. It aims to present the imperative introduction of Education for ethnic-racial relations in the school curricula from the perspective of decolonizing practices, recognition of subjects and sense of belonging. The text is part of the struggles against the silencing of racism and the confrontation of acts of violence that naturalize prejudice and discrimination. The research has a qualitative approach, whose instruments found support in Gil (2008) and Brandão (2003), and the content analysis was based on Bardin (2016). The precepts of Curricular Justice and the principles of Education for ethnic-racial relations form the theoretical framework that supports the analytical approaches here conducted. The article concludes by highlighting Curricular Justice and Education for ethnic-racial relations as feasible struggles to overcome racism. Keywords: Overcoming racism. Education for ethnic-racial relations. Curricular Justice.